Bilateral Trade and Food Security - Douglas Brooks; Benno Ferrarini; Eugenia Go (Asian Development Bank (ADB), 2013)
We analyze the relationship between food security and trade, focusing on food importers' exposure to sudden market failures from relying on a narrow range of international suppliers. We compute a bilateral import penetration index (BIPI), which gauges the degree to which a country depends on another for food imports. Food trade maps are drawn by the application of a force-directed algorithm that sorts through computed BIPIs and maps the nodes corresponding to the strength of bilateral ties between country pairs, thereby showing importers' vulnerabilities to disruptions in bilateral channels. Results suggest that measures aimed at diversifying supply sources reduce vulnerability.
hdl:11540/2297
Keywords: F13; Q17; Q18; 330; food security; trade; bilateral trade; agriculture; agriculture trade